Findings on the cultivation of potatoes in organic farming - Dvořák, Petr; Tomášek, Jaroslav (Acta Agraria Debreceniensis, 2011)
This paper explores the effectiveness of organic and plastic mulching for potato production in the Czech Republic. The mulching with chopped grass (GM) and black textile mulch (BTM) were compared to non-mulching control variant (C) with mechanical cultivation. Especially in plots with BTM were first formed ridges and covered by the black polypropylene non-woven textile and then they were planting. During vegetation the infestation of Colorado potato beetle (CPB), weeds biomass, course of soil temperature and soil water potential were assessed. The results showed that surface of GM had a positive effect on soil temperature reduction, soil water potential depression. This study also indicated a positive effect of GM on the larvae of CPB diminution, on the other hand higher incidence of larvae and higher defoliation was observed in BTM. GM had a significant effect on the yield of potatoes. The yield of ware potatoes was higher by 27 % higher on plots with GM and by 16 % lower on plots wit BTM in comparison with C. NeemAzal T/S decreased statistically significantly % of defoliation and increased yield of ware potatoes by 35 % in comparison with control.